Day 4 Thu, November 14, 2019 2019
DOI: 10.2118/197940-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Wettability and Hydration Properties of Shale using Ionic Liquids in Water-Based Drilling Fluids

Abstract: Hydration of shale formations during drilling operations have adverse effects on wellbore stability. The shale hydration resulted from the interactions between drilling fluid and swelling clay contents in the shale formations. This paper addresses the improvement of wettability and hydration properties of shale to enhance the wellbore stability during the drilling operations. The novel ionic liquid-based drilling fluids were used to alter the wettability and hydration properties of shale. The novel ionic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Ionic liquids are low melting point liquids possessing negligible vapour pressure (Bavoh et al 2020;Bera et al 2020). Research has shown the addition of ionic liquids affects the clay structure which in turn alters its wettability which results into the modification of the mud rheology and its filtration behaviour (Ahmad, et al 2019;Ahmed Khan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids are low melting point liquids possessing negligible vapour pressure (Bavoh et al 2020;Bera et al 2020). Research has shown the addition of ionic liquids affects the clay structure which in turn alters its wettability which results into the modification of the mud rheology and its filtration behaviour (Ahmad, et al 2019;Ahmed Khan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of nanoparticles in the water-based drilling fluids involves the plugging of micropores and makes a thin and impermeable filter cake on the walls of the wellbore, preventing the interaction of water with shale. Recently, the application of ionic liquids and surfactants as water-based drilling fluid additives was studied to enhance the shale inhibition performance …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of ionic liquids and surfactants as water-based drilling fluid additives was studied to enhance the shale inhibition performance. 35 Surfactants are commonly used in enhanced oil recovery (EOR) applications; nevertheless, the use of surfactants in drilling fluid applications is limited. 36,37 Surfactants are new materials used as clay inhibitors in the water-based drilling fluids to improve the shale inhibition performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several drilling fluids additives were employed as shale inhibitors from the last few decades to enhance drilling fluid inhibition properties. The reported shale inhibitors in the literature include polymers [ 25 , 26 , 27 ]; inorganic slats [ 28 ]; polymer nanocomposites [ 29 , 30 ]; glycols [ 31 , 32 ]; amines [ 33 , 34 ] and its derivatives, polymeric amines, dendrimers of amines [ 35 , 36 ], ionic liquids [ 37 ], nanoparticles [ 38 ], surface-modified nanoparticles [ 39 ], and surfactants [ 3 ]. The shale inhibition phenomenon is categorized into two classes, inhibition by physically sealing the micropores and small cracks, and chemical inhibition, in which inhibitor molecules encapsulate the shale surface to prevent the interaction of shale with water.…”
Section: Introductionmentioning
confidence: 99%